1997
DOI: 10.1021/ic9710263
|View full text |Cite
|
Sign up to set email alerts
|

A Neutral Spirocyclic Hexacoordinated Germanium(IV) Complex:  Hypervalent Germanium Compounds with Sulfur-Containing Eight-Membered Rings

Abstract: X-ray analysis of the complex [2,2‘-S-(4,6-tBu2C6H2O)2]2Ge reveals a hexacoordinated Ge atom with bonding of the transannular sulfur atoms in the eight-membered rings to germanium. An octahedral geometry about Ge is observed. 1H NMR spectral data are consistent with the hexacoordinate structure being maintained in solution. This six-coordinate Ge complex provides a model for the possible bonding and structure of TS's and intermediates in nucleophilic substitution reactions at Ge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…It has been shown that in the absence of donor atoms in the ortho position, the diaryl sulfide acts as monodentate with only sulfur coordinating with the metal center [3]. In the presence of donor groups (hydroxyl, thiol, imines, amides) at the ortho position, diaryl sulfides are known to coordinate with metals such as aluminum [4], palladium [5], nickel [6], platinum [7], ruthenium [8], iron [9], lanthanide [10], germanium [11] and zinc complexes [12] in a tridentate manner, whereby the sulfur is involved in coordination or bidentate binding with no sulfur coordination. Diaryl sulfides containing dicarboxylate as a donor group have not been subjected to detailed study.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in the absence of donor atoms in the ortho position, the diaryl sulfide acts as monodentate with only sulfur coordinating with the metal center [3]. In the presence of donor groups (hydroxyl, thiol, imines, amides) at the ortho position, diaryl sulfides are known to coordinate with metals such as aluminum [4], palladium [5], nickel [6], platinum [7], ruthenium [8], iron [9], lanthanide [10], germanium [11] and zinc complexes [12] in a tridentate manner, whereby the sulfur is involved in coordination or bidentate binding with no sulfur coordination. Diaryl sulfides containing dicarboxylate as a donor group have not been subjected to detailed study.…”
Section: Introductionmentioning
confidence: 99%
“…We thus sought to fulfil this gap by employing substituted 2,2 0 -thiobis(4,6-dialkylphenolate) dianions as tridentate ligands and systematically explore the chemistry and the potential catalytic activity of their group 13 metal compounds. Thioetherbisphenol ligands had previously been used to form phosphorous [26 -31], silicon [32], germanium [33] and titanium [34,35] compounds demonstrating that the coordination ability of the ligand can be tuned by the choice of substituients. Moreover, it has been demonstrated that replacement of the methylene bridge in bisphenolate titanium systems by a sulphur atom results in the improvement of the activity in olefin polymerization reactions [34 -38].…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to synthesize compound 1 by salt metathesis reaction between the lithium salt O(o-C 6 H 4 SLi) 2 and GeCl 4 , or with the use of GeCl 4 , the free ligand O(o-C 6 H 4 SH) 2 and an amine as an HCl acceptor (methods used in other cases) were unsuccessful [1][2][3]. Therefore, we decided to use Ge(O i Pr) 4 as the source of germanium because its reactivity is lower than that of GeCl 4 and thus the reaction can be easily controlled.…”
Section: Resultsmentioning
confidence: 99%
“…Only three spiro-dibenzogermocine complexes of the type [D(o-C 6 H 4 E) 2 ] 2 Ge (D = Se, S, P-Ph; E = O, S) [1][2][3] and two spiro-germocane complexes [D(CH 2 CH 2 S) 2 ] 2 Ge (D = O, S) [4] (Fig. 1) in which the germanium atom is hexacoordinated have been structurally characterized.…”
Section: Introductionmentioning
confidence: 99%